Surface-treated copper foil, its manufacturing method and negative electrode for secondary battery including same

A surface-treated copper foil with controlled needle-shaped copper particles addresses interfacial resistance and adhesive strength issues, enhancing the performance of lithium secondary batteries by reducing resistance and improving adhesion.

JP7620628B2Active Publication Date: 2025-01-23LOTTE ENERGY MATERIALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022532653
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-19
Filing Date
2019-12-20
Publication Date
2025-01-23
Estimated Expiration
2039-12-20

AI Technical Summary

Technical Problem

Lithium secondary batteries face issues of high interfacial resistance and reduced adhesive strength between the negative electrode current collector and active material, leading to decreased charge and discharge performance and potential detachment of the active material due to swelling or external impact.

Method used

A surface-treated copper foil with needle-shaped copper particles having a specific size and spacing, and optionally an anti-rust layer, is used as the negative electrode current collector, which is produced through a controlled electrolytic plating process to reduce interfacial resistance and enhance adhesive strength.

Benefits of technology

The surface-treated copper foil achieves significantly lower interfacial resistance and higher adhesive strength, improving the charge and discharge efficiency of secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620628000002
    Figure 0007620628000002
  • Figure 0007620628000003
    Figure 0007620628000003
  • Figure 0007620628000004
    Figure 0007620628000004
Patent Text Reader

Abstract

Disclosed is a surface-treated copper foil for use as a negative electrode current collector in a secondary battery, the surface-treated copper foil having, on at least one surface thereof, acicular copper particles with an average major axis of about 0.6 μm to about 2.0 μm spaced apart at intervals of about 1 μm to about 5 μm; a method for producing the same; and a negative electrode for a secondary battery including the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a surface-treated copper foil, a manufacturing method thereof, and a negative electrode for a secondary battery including the same, and more particularly to a surface-treated copper foil having low interfacial resistance with a negative electrode active material and excellent adhesive strength, a manufacturing method thereof, and a negative electrode for a secondary battery including the same. [Background technology]

[0002] A secondary battery is a type of energy conversion device that converts electrical energy into chemical energy, stores it, and then generates electricity by converting the chemical energy back into electrical energy when electricity is needed. Among the various secondary batteries, lithium secondary batteries are currently widely used due to their high operating voltage, high energy density, and excellent life characteristics.

[0003] A lithium secondary battery is composed of a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode is composed of a positive electrode current collector coated with a positive electrode active material layer, and the negative electrode is composed of a negative electrode current collector coated with a negative electrode active material layer, and electrolytic copper foil is mainly used as the negative electrode current collector. In such a negative electrode, the current collector and the active material made of different materials are in contact with each other, so that an interface resistance occurs, and the higher the interface resistance, the lower the charge / discharge performance and the lower the cell efficiency.

[0004] Meanwhile, the active material on the current collector may be partially detached due to deterioration, swelling, or external impact of the secondary battery. Specifically, the adhesion of the active material applied to the surface of the current collector is weakened due to physical forces such as deterioration, swelling, or external impact of the secondary battery, and gaps are generated at the contact surface between the current collector and the active material. As a result, the gaps between the active material and the current collector reduce the surface area through which current and electrons move, and the current and electrons tend to concentrate at specific points, which increases the internal resistance of the negative electrode. Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a surface-treated copper foil having low interfacial resistance with a negative electrode active material, a method for producing the same, and a negative electrode for a secondary battery including the same.

[0006] Another object of the present invention is to provide a surface-treated copper foil having excellent adhesive strength with a negative electrode active material, a method for producing the same, and a negative electrode for a secondary battery including the same. [Means for solving the problem]

[0007] 1. According to one aspect, there is provided a surface-treated copper foil for use as a negative electrode current collector for a secondary battery, which may have, on at least one surface of the copper foil, acicular copper particles having an average major axis of about 0.6 μm to about 2.0 μm spaced apart from each other at intervals of about 1 μm to about 5 μm.

[0008] 2. In the above 1, the aspect ratio of the copper particles may be about 1.5 to about 10.

[0009] 3. In the above 1 or 2, the surface-treated copper foil can have a thickness of about 1 μm to about 100 μm.

[0010] 4. In any one of 1 to 3 above, the surface-treated copper foil may have an interface resistance that is about 10% or more lower than that of an untreated copper foil.

[0011] 5. In any one of 1 to 4 above, the surface-treated copper foil has an interface resistance of about 0.0025 ohm / m 2 ~0.0032ohm / m 2 may be also possible.

[0012] 6. In any one of 1 to 5 above, the surface-treated copper foil may have an adhesive strength greater than that of an untreated copper foil by about 20% or more.

[0013] 7. In any one of 1 to 6 above, the surface-treated copper foil may have an adhesive strength of about 3 gf / mm to about 5 gf / mm.

[0014] 8. In any one of 1 to 7 above, the surface-treated copper foil may further include an inorganic anticorrosive layer, an organic anticorrosive layer, or a combination thereof, which covers each of the copper particles.

[0015] 9. In the above item 8, the inorganic anticorrosive layer may contain chromium (Cr), nickel (Ni), cobalt (Co), an alloy thereof, or a combination thereof, and the organic anticorrosive layer may contain an azole-based compound, a silane-based compound, or a combination thereof.

[0016] 10. According to another aspect, there is provided a method for producing a surface-treated copper foil according to any one of 1 to 9 above. The method includes immersing a copper foil in a primary electrolyte solution containing about 5 g / L to about 15 g / L of nickel salt and about 5 g / L to about 20 g / L of copper salt at a liquid temperature of about 25° C. to about 45° C. and a current of about 1 A / dm 2 ~5A / dm 2 After the primary plating for about 1 to about 5 seconds at a current density of about 25 to about 45° C., the plate is immersed in a secondary electrolyte containing about 40 g / L to about 70 g / L of copper salt and about 100 g / L to about 150 g / L of sulfuric acid at a liquid temperature of about 25° C. to about 45° C. and a current density of about 10 A / dm 2 ~20A / dm 2 The step of secondary plating may include plating at a current density of about 1 to about 5 seconds.

[0017] 11. According to yet another aspect, there is provided a negative electrode for a secondary battery, the negative electrode being formed by coating a negative electrode active material on the surface-treated copper foil of any one of 1 to 9 above or the surface-treated copper foil produced by the method of 10 above.

[0018] 12. In the above 11, the negative electrode active material can include carbon, a metal, a metal oxide, a metal carbide, or a combination thereof. Effect of the Invention

[0019] The present invention has an effect of providing a surface-treated copper foil having low interfacial resistance with a negative electrode active material and excellent adhesive strength, a method for producing the same, and a negative electrode for a secondary battery including the same. [Brief description of the drawings]

[0020] [Figure 1] FIG. 2 is a diagram showing SEM images of the surface-treated copper foils of Example 1(a), Comparative Example 1(b), Comparative Example 2(c), and Comparative Example 3(d). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] In this specification, the singular expression includes the plural expression unless the context clearly indicates a different meaning.

[0022] The same reference numerals refer to the same elements throughout the specification. Furthermore, in describing the present invention, if it is determined that a detailed description of related prior art may unnecessarily obscure the gist of the present invention, the detailed description thereof will be omitted.

[0023] When the positional relationship of two parts is described as "on top of," "at the top of," "at the bottom of," "beside," etc., one or more other parts are located between the two parts, unless "directly" or "immediately" is used.

[0024] In this specification, the terms "comprise" or "have" mean the presence of features or components described in the specification, but do not preclude the possibility that one or more other features or components may be added.

[0025] When interpreting elements, they are interpreted as including a margin of error even if there is no other explicit description.

[0026] In this specification, the term "to" in the expression "a to b" indicating a numerical range is defined as ≧a and ≦b.

[0027] In this specification, the "aspect ratio" may refer to the ratio of the longest linear distance to the shortest linear distance in the cross section of a copper particle (major axis / minor axis or length / width). The longest linear distance in the cross section of a copper particle is referred to as the major axis, and the shortest linear distance is referred to as the minor axis.

[0028] As used herein, "copper particle separation or distance" refers to the shortest separation or distance between each copper particle.

[0029] In this specification, the term "interface resistance value" refers to a value measured by coating a negative electrode active material slurry, which is a mixture of 6 g of artificial graphite, 6.3 g of CMC (carboxymethyl cellulose) (2% aqueous solution), 0.32 g of SBR (styrene-butadiene rubber), and 1 ml of distilled water, on a surface-treated copper foil (15 cm x 15 cm) to a thickness of 60 μm to 80 μm using a doctor blade, drying at 130° C. for 1 hour, and then using an interface resistance evaluation device under measurement conditions of a current of 10 mA, speed: normal, and voltage range: 0.5 V.

[0030] In this specification, the term "adhesive strength value" refers to a value obtained by coating a negative active material on a surface-treated copper foil, drying the coated surface of the negative active material, attaching double-sided tape to the surface of the negative active material, and measuring the 90° peel strength using a tensile tester.

[0031] The present inventors have conducted extensive research into copper foil for use as a negative electrode current collector capable of improving the charge / discharge efficiency of a secondary battery, and as a result have discovered that a surface-treated copper foil for use as a negative electrode current collector of a secondary battery contains needle-shaped copper particles on at least one surface of the copper foil, and the average major axis of each of the copper particles is about 0.6 μm to about 2.0 μm (for example, about 0.6 μm, about 0.7 μm, about 0.8 μm, about 0.9 μm, etc.). , about 1.0 μm, about 1.1 μm, about 1.2 μm, about 1.3 μm, about 1.4 μm, about 1.5 μm, about 1.6 μm, about 1.7 μm, about 1.8 μm, about 1.9 μm or about 2.0 μm, and about 1 μm to about 5 μm (e.g., about 1.1 μm, about 1.2 μm, about 1.3 μm, about 1.4 μm, about 1.5 μm, about 1.6 μm, about 1.7 μm, about 1.8 μm, about 1. 9μm, about 2μm, about 2.1μm, about 2.2μm, about 2.3μm, about 2.4μm, about 2.5μm, about 2.6μm, about 2.7μm, about 2.8μm, about 2.9μm, about 3μm, Approximately 3.1μm, approximately 3.2μm, approximately 3.3μm, approximately 3.4μm, approximately 3.5μm, approximately 3.6μm, approximately 3.7μm, approximately 3.8μm, approximately 3.9μm, approximately 4μm, approximately 4.1μm, approximately 4. The present invention has been completed based on the findings that, when the copper particles are spaced apart from each other by an interval of about 2 μm, about 4.3 μm, about 4.4 μm, about 4.5 μm, about 4.6 μm, about 4.7 μm, about 4.8 μm, about 4.9 μm, or about 5 μm, the copper particles can cover the negative active material better than spherical, polygonal, etc. copper particles, resulting in low interfacial resistance with the negative active material and high adhesive strength. According to one embodiment, the average major axis of the acicular copper particles may be about 0.7 μm to about 1.6 μm (e.g., about 0.7 μm to about 1.5 μm) and the spacing may be about 1 μm to about 4.5 μm (e.g., about 1.2 μm to about 4.1 μm), but is not limited thereto.

[0032] The method for forming the above-mentioned acicular copper particles on the surface of the copper foil is not particularly limited, but for example, the acicular copper particles may be formed by electrolytic plating the copper foil twice. The first electrolyte solution contains about 5 g / L to about 15 g / L of nickel salt (e.g., about 5 g / L, about 6 g / L, about 7 g / L, about 8 g / L, about 9 g / L, about 10 g / L, about 11 g / L, about 12 g / L, about 13 g / L, about 14 g / L, or about 15 g / L, for example, about 8 g / L to about 14 g / L) and about 5 g / L to about 20 g / L of copper salt (e.g., about 5 g / L, about 6 g / L, about 7 g / L, about 8 g / L, about 9 g / L, about 10 g / L, about 15 g / L, or about 15 g / L). An aqueous solution containing about 1 g / L, about 12 g / L, about 13 g / L, about 14 g / L, about 15 g / L, about 16 g / L, about 17 g / L, about 18 g / L, about 19 g / L or about 20 g / L, for example, 10 g / L to 17 g / L) adjusted to a pH of about 1 to about 5 (e.g., about 1, about 2, about 3, about 4 or about 5, for example, about 2 to about 4) can be used, and within this range, needle-shaped copper particle seeds can be smoothly formed. The secondary electrolyte may be an aqueous solution containing about 40 g / L to about 70 g / L of copper salt (e.g., about 40 g / L, about 45 g / L, about 50 g / L, about 55 g / L, about 60 g / L, about 65 g / L, or about 70 g / L, or another example, about 45 g / L to about 60 g / L) and about 100 g / L to about 150 g / L of sulfuric acid (e.g., about 100 g / L, about 105 g / L, about 110 g / L, about 115 g / L, about 120 g / L, about 125 g / L, about 130 g / L, about 135 g / L, about 140 g / L, about 145 g / L, about 150 g / L, or another example, about 120 g / L to about 140 g / L). In this range, acicular copper particles may be successfully formed on the seed. Examples of nickel salts include, but are not limited to, nickel sulfate, nickel nitrate, nickel chloride, nickel acetate, etc., which may be used alone or in combination of two or more. Examples of copper salts include, but are not limited to, copper sulfate, copper nitrate, copper chloride, copper acetate, etc., which may be used alone or in combination of two or more.The primary electrolytic plating is carried out, for example, by immersing an insoluble electrode as a positive electrode and an untreated copper foil as a negative electrode in a primary electrolytic solution at a solution temperature of about 25° C. to about 45° C. (e.g., about 25° C., about 30° C., about 35° C., about 40° C., or about 45° C.) and a current of about 1 A / dm. 2 ~5A / dm 2 (For example, about 1A / dm 2 , about 2A / dm 2 , about 3A / dm 2 , about 4A / dm 2 Or about 5A / dm 2 The second electrolytic plating may be performed by electrolysis at a current density of about 1 to about 5 seconds (e.g., about 1 second, about 2 seconds, about 3 seconds, about 4 seconds, or about 5 seconds) at a current density of about 10 A / dm. The second electrolytic plating may be performed, for example, by immersing the insoluble electrode as a positive electrode and the copper foil that has been electrolytically plated as a negative electrode in a second electrolytic solution at a solution temperature of about 25° C. to about 45° C. (e.g., about 25° C., about 30° C., about 35° C., about 40° C., or about 45° C.) and a current density of about 10 A / dm. 2 ~20A / dm 2 (For example, about 10A / dm 2 , about 11A / dm 2 , about 12A / dm 2 , about 13A / dm 2 , about 14A / dm 2 , about 15A / dm 2 , about 16A / dm 2 , about 17A / dm 2 , about 18A / dm 2 , about 19A / dm 2 Or about 20A / dm 2 ) for about 1 second to about 5 seconds (for example, about 1 second, about 2 seconds, about 3 seconds, about 4 seconds, or about 5 seconds), but is not limited thereto.

[0033] According to an embodiment, the aspect ratio of the acicular copper particles may be about 1.5 to about 10 (e.g., about 1.5, about 2, about 2.5, about 3, about 3.5, about 4, about 4.5, about 5, about 5.5, about 6, about 6.5, about 7, about 7.5, about 8, about 8.5, about 9, about 9.5, or about 10). In this range, it is possible to have low interfacial resistance and excellent adhesive strength with the negative electrode active material. For example, the aspect ratio of the acicular copper particles may be about 1.5 to about 7, or another example, about 2 to about 5, but is not limited thereto.

[0034] According to an embodiment, the short diameter of the acicular copper particles may be about 0.2 μm to about 0.6 μm (e.g., 0.2 μm, about 0.3 μm, about 0.4 μm, about 0.5 μm, or about 0.6 μm). Within this range, low interfacial resistance and excellent adhesive strength with the negative electrode active material may be obtained. For example, the short diameter of the acicular copper particles may be about 0.3 μm to about 0.5 μm, but is not limited thereto.

[0035] According to an embodiment, the surface-treated copper foil may have a thickness of about 1 μm to about 100 μm. In this range, the surface-treated copper foil may be suitable as a negative electrode current collector. For example, the thickness of the surface-treated copper foil may be about 3 μm to about 80 μm, and another example, about 5 μm to about 60 μm, but is not limited thereto.

[0036] According to an embodiment, the surface-treated copper foil may have an interface resistance that is about 10% or more lower than that of an untreated copper foil. For example, the surface-treated copper foil may have an interface resistance that is about 10% to about 100% (e.g., about 10%, about 20%, about 30%, about 40%, about 50%, about 60%, about 70%, about 80%, about 90% or about 100%), or another example, about 10% to about 30% lower than that of an untreated copper foil, but is not limited thereto.

[0037] According to one embodiment, the surface-treated copper foil has an interface resistance of 0.0025 ohm / m 2 ~0.0032ohm / m 2 (For example, about 0.0025 ohm / m 2 , about 0.0026ohm / m2 , about 0.0027ohm / m 2 , about 0.0028ohm / m 2 , about 0.0029ohm / m 2 , about 0.0030ohm / m 2 , about 0.0031ohm / m 2 or about 0.0032 ohm / m 2 For example, the interface resistance of the surface-treated copper foil may be about 0.0025 ohm / m 2 ~0.0031ohm / m 2 , for example, about 0.0027 ohm / m 2 ~0.0031ohm / m 2 However, the present invention is not limited to this.

[0038] According to an embodiment, the surface-treated copper foil may have an adhesive strength that is about 20% or more greater than that of an untreated copper foil, for example, the surface-treated copper foil may have an adhesive strength that is about 20% to about 100% (e.g., about 20%, about 30%, about 40%, about 50%, about 60%, about 70%, about 80%, about 90% or about 100%) greater than that of an untreated copper foil, or in other examples, about 20% to about 50% greater, but is not limited thereto.

[0039] According to an embodiment, the surface-treated copper foil may have an adhesive strength of about 3 gf / mm to about 5 gf / mm (e.g., about 3 gf / mm, about 3.1 gf / mm, about 3.2 gf / mm, about 3.3 gf / mm, about 3.4 gf / mm, about 3.5 gf / mm, about 3.6 gf / mm, about 3.7 gf / mm, about 3.8 gf / mm, about 3.9 gf / mm, about 4 gf / mm, about 4.1 gf / mm, about 4.2 gf / mm, about 4.3 gf / mm, about 4.4 gf / mm, about 4.5 gf / mm, about 4.6 gf / mm, about 4.7 gf / mm, about 4.8 gf / mm, about 4.9 gf / mm, or about 5 gf / mm). For example, the adhesive strength of the surface-treated copper foil may be, but is not limited to, about 3 gf / mm to about 4.5 gf / mm, and as another example, about 3 gf / mm to about 4 gf / mm.

[0040] According to an embodiment, the surface-treated copper foil may further include an anticorrosive layer covering each of the acicular copper particles. The anticorrosive layer may be an inorganic anticorrosive layer, an organic anticorrosive layer, or a combination thereof, and the number of anticorrosive layers is not particularly limited. The inorganic anticorrosive layer may include, for example, chromium (Cr), nickel (Ni), cobalt (Co), an alloy thereof, or a combination thereof, and the organic anticorrosive layer may include an azole-based compound (e.g., a benzotriazole-based compound), a silane-based compound, or a combination thereof. According to an embodiment, the anticorrosive layer may include a chromate anticorrosive layer, which may be formed by treating with a solution containing, for example, chromic anhydride, chromic acid, dichromate, chromate salt, or a combination thereof, but is not limited thereto.

[0041] The above-mentioned surface-treated copper foil may be used as a negative electrode current collector for a secondary battery, and in this case, it can provide low interfacial resistance and excellent adhesive strength with the negative electrode active material.

[0042] According to another aspect, there is provided a negative electrode for a secondary battery, the negative electrode being formed by coating a negative electrode active material on the surface-treated copper foil described above.

[0043] The type of the negative electrode active material is not particularly limited, and various known negative electrode active materials may be used without limitation. For example, the negative electrode active material may include carbon (e.g., artificial graphite, natural graphite, etc.), metal powder (e.g., lithium powder, tin powder, silicon powder, etc.), metal oxide (e.g., tin oxide, silicon oxide, etc.), metal carbide (e.g., silicon carbide, etc.), or a combination thereof.

[0044] According to yet another aspect, there is provided a secondary battery including the above-described negative electrode for a secondary battery.

[0045] The present invention will be described in more detail below with reference to examples. However, these are presented as preferred examples of the present invention and should not be construed as limiting the present invention in any sense.

[0046] Working Example

[0047] Example 1 A copper foil (Iljin Materials Co., Ltd.) with a thickness of 8 μm was immersed in a primary electrolyte solution containing 10 g / L of nickel sulfate and 10 g / L of copper sulfate at a temperature of 30°C, a pH of 2.5, and 2 A / dm 2 After the first plating for 3 seconds at a current density of 14A / dm, the plate was immersed in a secondary electrolyte containing 65g / L copper sulfate and 120g / L sulfuric acid at a liquid temperature of 30°C and 2 The secondary plating was performed for 3 seconds at a current density of 10000. The electrolytically plated copper foil was then immersed in an aqueous solution containing 2 g / L of chromic acid at 30°C for 3 seconds and rinsed with water to form an anti-corrosive layer, thereby producing a surface-treated copper foil.

[0048] Example 2 A surface-treated copper foil was prepared in the same manner as in Example 1, except that the content of nickel sulfate in the first plating was changed to 11 g / L.

[0049] Working Example 3 A surface-treated copper foil was prepared in the same manner as in Example 1, except that the content of nickel sulfate in the first plating was changed to 12 g / L.

[0050] Example 4 A surface-treated copper foil was prepared in the same manner as in Example 1, except that the content of nickel sulfate in the first plating was changed to 13 g / L.

[0051] Comparative Example 1 A surface-treated copper foil was manufactured in the same manner as in Example 1, except that the first and second electrolytic plating were not performed.

[0052] Comparative Example 2 A surface-treated copper foil was prepared in the same manner as in Example 1, except that the content of copper sulfate in the first plating was changed to 30 g / L.

[0053] Comparative Example 3 The surface-treated copper foil was manufactured in the same manner as in Example 1, except that nickel sulfate was not added during the first plating.

[0054] The physical properties of the surface-treated copper foils prepared in the Examples and Comparative Examples were evaluated using the following physical property evaluation methods, and the results are shown in Table 1 below.

[0055] Physical property evaluation method (1) Measurement of the average long diameter of copper particles (unit: μm) and the average spacing between copper particles (unit: μm): The surface of the surface-treated copper foil was photographed at 5,000 times magnification using an electron scanning microscope, and the long diameter and spacing between copper particles were measured for 50 copper particles within an area of ​​100 μm x 100 μm, and the average value was calculated.

[0056] (2) Interface resistance measurement (unit: ohm / m 2 ): A negative electrode active material slurry was prepared by mixing 6 g of artificial graphite (MAG-D, Hitachi Chem), 6.3 g of CMC (carboxymethyl cellulose) (2% aqueous solution), 0.32 g of SBR (styrene-butadiene rubber), and 1 ml of distilled water. The slurry was coated to a thickness of 60 μm to 80 μm on a surface-treated copper foil (15 cm x 15 cm) using a doctor blade (Micrometer Adjustable Film Applicator, Welcos), and dried at 130°C for 1 hour. The interface resistance was then measured using an interface resistance evaluation device (XF057, Hioki) under the following measurement conditions: current: 10 mA, speed: normal, voltage range: 0.5 V.

[0057] (3) Adhesive strength measurement (unit: gf / mm): After coating and drying the negative active material on the surface-treated copper foil in the same manner as in the measurement of interfacial resistance, a double-sided tape was attached to the surface on which the negative active material was coated to prepare a tensile test specimen of 30 mm x 70 mm (width x length). The 90° peel strength was measured at a speed of 50.8 mm / min using a tensile tester.

[0058] [Table 1]

[0059] As can be seen from Table 1, the surface-treated copper foils of Examples 1 to 4, in which the shape, average major axis, and average separation distance of the copper particles are within the ranges of the present invention, have lower interface resistance and higher adhesive strength than the surface-treated copper foils of Comparative Examples 1 to 3, in which the shape, average major axis, and average separation distance of the copper particles are not within the ranges of the present invention. Therefore, it can be seen that the surface-treated copper foils of the present invention are particularly suitable as negative electrode current collectors for secondary batteries.

[0060] The present invention has been described above with reference to the embodiments. Those skilled in the art will understand that the present invention can be embodied in modified forms without departing from its essential characteristics. Therefore, the disclosed embodiments should be considered from an explanatory perspective, not a limiting one. The scope of the present invention is defined in the claims, not the above description, and all differences within the scope of the equivalents thereto should be construed as being included in the present invention.

Claims

1. A surface-treated copper foil for use as a negative electrode current collector of a secondary battery, comprising: on at least one surface of the copper foil, needle-shaped copper particles having an average major axis of 0.6 μm to 2.0 μm spaced apart from each other at intervals of 1 μm to 5 μm; and an aspect ratio of the copper particles being 2 to 10.

2. The surface-treated copper foil according to claim 1 , wherein the surface-treated copper foil has a thickness of 1 μm to 100 μm.

3. The surface-treated copper foil according to claim 1 or 2, further comprising an inorganic anticorrosive layer, an organic anticorrosive layer, or a combination thereof, which coats each of the copper particles.

4. The inorganic anticorrosive layer comprises chromium (Cr), nickel (Ni), cobalt (Co), an alloy thereof, or a combination thereof; The surface-treated copper foil according to claim 3 , wherein the organic anticorrosive layer comprises an azole-based compound, a silane-based compound, or a combination thereof.

5. The copper foil is immersed in a primary electrolyte solution containing 5 g / L to 15 g / L of nickel salt and 5 g / L to 20 g / L of copper salt at a liquid temperature of 25° C. to 45° C. and a current of 1 A / dm 2 ~5A / dm 2 After the primary plating for 1 to 5 seconds at a current density of 10 A / dm, the plate is immersed in a secondary electrolyte containing 40 g / L to 70 g / L of copper salt and 100 g / L to 150 g / L of sulfuric acid at a solution temperature of 25° C. to 45° C. and a current density of 10 A / dm 2 ~20A / dm 2 5. The method for producing a surface-treated copper foil according to claim 1, further comprising the step of: performing a secondary plating at a current density of 0.1 to 1000 .mu.m for 1 to 5 seconds.

6. 5. A negative electrode for a secondary battery, comprising the surface-treated copper foil according to claim 1, coated with a negative electrode active material.

7. The negative electrode for a secondary battery according to claim 6 , wherein the negative electrode active material comprises carbon, a metal, a metal oxide, a metal carbide, or a combination thereof.

Citation Information

Patent Citations

  • Filler material, wiring substrate using the same, and method for manufacturing of wiring substrate

    JP2005223312A

  • Copper foil with carrier

    JP2009214308A

  • Power collector, its manufacturing method, negative electrode body, its manufacturing method, and lithium ion secondary battery

    JP2009266492A

  • Rolled copper foil excellent in shearing processability and electrode collector using this, negative electrode plate, and secondary battery

    JP2011070830A

  • Electrolytic copper foil, electrolytic copper foil for lithium ion secondary battery, electrode for lithium ion secondary battery using the electrolytic copper foil, and lithium ion secondary battery using the electrode

    JP2012033475A